Operations optimization model under the PDCA APPROACH to increase the number of visitors in a shopping mall: an empirical research in Peru - Mosqueira Stucchi, Alejandro Eduardo (2022)
The number of visitors of a shopping center has a critical impact on its annual turnover, so a small number of such visitors is a major problem for participants in this industry. In the present study, a specific shopping center in Peru that presents this problem was chosen and a model was proposed to improve this indicator. For this, the PDCA cycle is used together with tools such as CRM, Digital Marketing and the SCRUM methodology. After its application, the results of using the Arena Program show a 7% increase in the number of visits and an increase in billing of 13.4%. Therefore, this model can be applied to other companies within the industry which seek to improve said indicators and, with that, their performance.